2014
DOI: 10.2174/1875399x01407010002
|View full text |Cite
|
Sign up to set email alerts
|

Arresting a Struggling Subject; Does the Forthcoming Police Officers Physical Fitness have an Impact on the Outcome?

Abstract: Handling a struggling subject has been pointed out as one of the maximal physical exertions of police work. However, the relationship between general physical fitness and the ability to manage an intractable subject is only scarcely examined. Therefore, the main purpose of this study was to examine how general physical fitness correlates with the forthcoming police officers' ability to handle in a simulated arrest handling test. Nineteen male police students voluntarily agreed to participate. Four physical tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Additional influences on the increased self-efficacy among some recruits included participation in additional martial arts training, and to a larger degree, both Academy fitness training and additional fitness training outside the Academy. This highlights the significance of fitness to an officer's perceptions of their self-defense abilities, although many studies have indicated that actual fitness training is often not maintained after the Academy [Anderson, Plecas & Segger 2001;Anderson, Cychosz & Franke 2003;Bissett, Bissett & Snell 2012;Dillern, Jenssen, Lagestad, Nygård & Ingebrigtsen 2014;Orr et al 2018]. Nevertheless, the results of this study indicate that Academy training provides a solid foundation for officers to start their careers with a healthy level of confidence in their abilities to handle violent, non-lethal encounters when necessary.…”
Section: Martialmentioning
confidence: 72%
“…Additional influences on the increased self-efficacy among some recruits included participation in additional martial arts training, and to a larger degree, both Academy fitness training and additional fitness training outside the Academy. This highlights the significance of fitness to an officer's perceptions of their self-defense abilities, although many studies have indicated that actual fitness training is often not maintained after the Academy [Anderson, Plecas & Segger 2001;Anderson, Cychosz & Franke 2003;Bissett, Bissett & Snell 2012;Dillern, Jenssen, Lagestad, Nygård & Ingebrigtsen 2014;Orr et al 2018]. Nevertheless, the results of this study indicate that Academy training provides a solid foundation for officers to start their careers with a healthy level of confidence in their abilities to handle violent, non-lethal encounters when necessary.…”
Section: Martialmentioning
confidence: 72%
“…Special police officers are required to have a strong, muscular, and robust body (Araujo et al, 2018;Dillern et al, 2014;J. Esteves, Andrade, Andreato, & Morais, 2014;Lockie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, affecting the arrest of a struggling suspect is one of the most strenuous physical tasks that an officer might encounter. 10 These encounters may even turn into life-threatening situations.…”
Section: Literature Review On Physical Health Benefits and Barriersmentioning
confidence: 99%